Optimizing healthy ageing in disadvantaged communities: insights into older people's use of health and social care services - Josephine Tetley (MDPI AG, 2012)
The European Year of Healthy Ageing recognizes that health care systems need to be improved and reorganized if services are to optimize the opportunities for people to stay healthy and well in their own homes for as long as possible. However, current services tend to be fragmented and insensitive to the needs of older people and their carers resulting in services being underused or refused leading to increased admissions into acute hospital care that could have been prevented. The main aim of the study reported in this paper was to identify the factors that affected older peoples’ decision and choice-making processes, when using or contemplating the use of care services. Using a constructivist methodology, this study used participant observation and 23 interviews in three study settings: an African Caribbean support service, day centers for people with memory and cognition problems and luncheon clubs for older people. An inductive analysis of the data revealed that when older community dwelling people found themselves struggling with certain aspects of their daily care needs; they used adapting, coping and seeking as strategies to manage. Additional issues of how well services were able to meet individual’s aspirations for care and support were identified through themes of match-mismatch, fair-unfair, independence-dependence. The findings reported in this study provide important insights as to how people’s needs are complex yet are negatively affected by rigid state controlled services that ultimately affect individual decisions to use or refuse services.